Application of Murabahah Operations on Gold Savings Products on Customer Deposit Fund Profits at Bank Syariah Indonesia (Case Study at Bank Syariah Indonesia Panyabungan Branch Office) - Pulungan, Rahmad; Syakir, Ahmad; Anggraimi, Tuti (Golden Ratio of Finance Management, 2025)
This study aims to determine the "Analysis of Murabahah Operations on Gold Savings Products Against the Profits of Customer Trust Funds at Bank Syariah Indonesia (Case Study of Bank Syariah Indonesia KCP Panyabungan)". This research was conducted at Bank Syariah Indonesia KCP Panyabungan. The method in this study uses qualitative methods with the form of data research (field research). The results showed that operations on gold savings products at Bank Syariah Indonesia KCP Panyabungan use murabahah contracts, but also wadi'ah and istishna' contracts, and the analysis of murabahah operations on gold savings products on deposit fund profits at Bank Syariah Indonesia KCP Panyabungan shows that murabahah contracts are used in sale and purchase transactions on gold savings products with this savings model has special characteristics that make it unique.